KEMAMPUAN PENGETAHUAN EKOLOGIS DAN SIKAP PEDULI LINGKUNGAN SISWA - Novitasari, Aulia (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
Growing awareness of environmental sustainability has emerged as a significant challenge in the modern era, particularly for the younger generation as agents of change. Education plays a vital role in fostering environmental literacy to develop individuals who are both knowledgeable and environmentally conscious. This study aims to analyze students’ ecological knowledge and environmental care attitudes in biology learning at SMA Muhammadiyah 2 Bandar Lampung. The research employed a descriptive quantitative method, with a sample of 65 students selected through purposive sampling from a population of 212. Data were collected using questionnaires and tests developed based on indicators of ecological knowledge and environmental care. The results indicate that students’ ecological knowledge falls into the “good” category, with a score of 66.15%, reflecting a satisfactory understanding of ecosystems, biodiversity, and environmental threats. Similarly, students’ environmental care attitudes also fall into the “good” category, with a score of 67.33%, demonstrating awareness and commitment to environmental preservation.